Camera crew setting up a set; Susanna is near a tree with laundry hanging on a line - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1958)
The plot of La Strada Lunga un Anno is divided into four major episodes, which correspond to the four seasons, beginning in autumn. These episodes are framed by an introduction and an epilogue which serve to identify the moral of the fable.
Keywords: Girotti, Massimo, 1918-2003; Italy -- Social conditions -- 1945-1976 -- Drama; Italy -- Social life and customs -- 1945--- Drama; Motion picture actors and actresses -- Italy; Motion picture producers and directors -- Italy; Motion pictures -- Italy -- History -- Sources; Pampini, Silvana, 1925-; Rossi-Drago, Eleanora, 1925-2007; Sotlar, Bert, 1921-1992; Stills (motion pictures)